Abitare al margine - Formato, Enrico (Mechane, 2023)
The essay juxtaposes modern and post-modern living with the landscape: A space of production of differences and of liberation from the biolithic control consolidated by the traditional architecture and town planning. What emerges is the “landscape turn” which, by subverting the methods and techniques of traditional spatial design, shifts the focus on uses, on processes (including informal ones), on the pure materiality of objects and relations. Such space is topologically and structurally “on the edge”, has no stable centre, nor closed boundaries; it is defined in a dimension always auroral, temporary, eventual. It can be intended as reserve or as a forest, or even be characterised by the emergence of new forms of civic use. Its position is on the fringe – between ‘houses’ and ‘corridors’ – at the points of friction between divergent forces, in the spaces of the post-metropolis, now largely uninhabited, harbingers of new habitability.